Performance evaluation of CI engine with Rice bran and Pungamia oil-Diesel blends as Alternative fuel. (International Journal of Engineering and Computer Science, 2015)
Petroleum products resources are limited and their consumption is increasing very fast with globalization. Diesel consumption is about 45% of the total consumption of petroleum products. Over the last 15 years the demand for petroleum products in India has risen and the situation could be more difficult for diesel engines. Apart from conservation there is a global threat to the environment due to polluting nature of conventional fuels. The solution to these twin problems will be utilizing the vegetable oils. A lot of research is going on the potential use of many vegetable oils. This paper provides detailed information, based on experimental work, on the use of rice bran and pongamia-oil as bio fuel. Various performance tests were carried out by blending rice bran and pongamia-oil as 5%, 10%, 15% with diesel and the results were found to be convincing with all blend ratios. More effective output was obtained with 15% blend